Endothelial cell metabolic memory causes cardiovascular dysfunction in diabetes. Issue 1 (23rd January 2021) - Yao, Yufeng; Song, Qixue; Hu, Changqing; Da, Xingwen; Yu, Yubing; He, Zuhan; Xu, Chengqi; Chen, Qiuyun; Wang, Qing K
Abstract: Aims : The aim of this study was to identify the molecular mechanism for hyperglycaemia-induced metabolic memory in endothelial cells (ECs), and to show its critical importance to development of cardiovascular dysfunction in diabetes. Methods and results : Hyperglycaemia induces increased nuclear factor-κB (NF-κB) signalling, up-regulation of miR-27a-3 p, down-regulation of nuclear factor erythroid-2 related factor 2 (NRF2) expression, increased transforming growth factor-β (TGF-β) signalling, down-regulation of miR-29, and induction of endothelial-to-mesenchymal transition (EndMT), all of which are memorized by ECs and not erased when switched to a low glucose condition, thereby causing perivascular fibrosis and cardiac dysfunction. Similar metabolic memory effects are found for production of nitric oxide (NO), generation of reactive oxygen species (ROS), and the mitochondrial oxygen consumption rate in two different types of ECs. The observed metabolic memory effects in ECs are blocked by NRF2 activator tert-butylhydroquinone and a miR-27a-3p inhibitor. In vivo, the NRF2 activator and miR-27a-3p inhibitor block cardiac perivascular fibrosis and restore cardiovascular function by decreasing NF-κB signalling, down-regulating miR-27a-3 p, up-regulating NRF2 expression, reducing TGF-β signalling, and inhibiting EndMT during insulin treatment of diabetes in streptozotocin-induced diabetic mice, whereas insulin alone does not improve cardiac function. Conclusions : Our data indicate that disruption of hyperglycaemia-induced EC metabolic memory is required for restoring cardiac function during treatment of diabetes, and identify a novel molecular signalling pathway of NF-κB/ miR-27a-3p /NRF2/ROS/TGF-β/EndMT involved in metabolic memory. Graphical Abstract: